2004
DOI: 10.1002/jcb.20333
|View full text |Cite
|
Sign up to set email alerts
|

High hydrostatic pressure inhibits the biosynthesis of eukaryotic elongation factor‐2

Abstract: High continuous hydrostatic pressure is known to inhibit the total cellular protein synthesis. In this study, our goal was to identify pressure-regulated proteins by using two dimensional gel electrophoresis and mass spectrometry. This analysis showed that under 30 MPa continuous hydrostatic pressure the biosynthesis of eukaryotic elongation factor-2 (eEF-2) was inhibited both in HeLa carcinoma and T/C28a4 chondrocytic cell lines. Western blot analysis of HeLa cells revealed that the cellular protein level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…It has been shown that HHP affects all levels of cellular physiology targeting cellular organization, transcription, translation, protein conformation, enzyme activity, and membrane function (12)(13)(14)(15). This knowledge has permitted preliminary interpretations of the mechanisms of HHP-induced cell death and stress response and has raised the possibility of using the high pressure response of cells and microorganisms as a novel approach to study biological systems and use cells as factories in HHP biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that HHP affects all levels of cellular physiology targeting cellular organization, transcription, translation, protein conformation, enzyme activity, and membrane function (12)(13)(14)(15). This knowledge has permitted preliminary interpretations of the mechanisms of HHP-induced cell death and stress response and has raised the possibility of using the high pressure response of cells and microorganisms as a novel approach to study biological systems and use cells as factories in HHP biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Later experiments with HeLa cells indicated that the increase in heat shock protein 90 was mainly due to change in its b-isoform [84]. High hydrostatic pressure also inhibits protein synthesis in general [85], which may be partly explained by decreased level of intracellular eukaryotic elongation factor-2, first observed by proteomic analysis shown in Fig. 3 [86]. Products secreted by chondrocytes can also be analyzed from culture medium of explant cultures [62,87], although many of the proteins present in the sample are not necessarily chondrocyte-derived but may originate from plasma, synovial fluid or blood cells [62].…”
Section: Proteomics In the Basic Science Of Bone Bone Cells Cartilamentioning
confidence: 98%
“…Continuous high pressure inhibits macromolecule synthesis and secretion, reduces the steady-state level of aggrecan mRNA, alters the shape of the Golgi apparatus, and disturbs the stress fibre organisation of microfilaments (Symington et al 1991;Hall et al 1993;Parkkinen et al 1993bParkkinen et al , 1995Lammi et al 1994;Jortikka et al 2000). Stress response has been detected in chondrocytic cells submitted to continuous high hydrostatic pressure regimes (Table 3) (Kaarniranta et al 1998;Elo et al 2000Elo et al , 2005Kaarniranta et al 2000). Several heat shock proteins (HSP) are up-regulated, among which Hsp70 is the most intensively induced.…”
Section: Effects Of Pressure On Gene Expressionmentioning
confidence: 99%
“…Specifically, it has been shown that exposure to pressure higher than the native pressure experienced by an organism triggers an increase in the expression of heat shock proteins (HSP) (Elo et al 2000;Sironen et al 2002;Elo et al 2005), which are known to be involved in general stress situations (Feder and Hofmann 1999). In parallel, repression of cell cycle control factors has also been observed, explaining cellular growth arrest in relation to pressure stresses.…”
Section: Introductionmentioning
confidence: 97%